Functional nanoparticle developments for 3D-printed biodegradable implants- A comprehensive review - Amran Hossain; Md Rifat Hossain Shuvo; Safiullah Khan; Abu Sad MD Sayem; Safiul Islam; Nayem Hossain (Results in Surfaces and Interfaces)
One of the groundbreaking methods within biomedical engineering involves the application of functional nanoparticles in 3D-printed biodegradable implants. This work discusses the prospects of integrating nanoparticles and additive production techniques to improve medical implants' performance and therapeutic potency. Increased mechanical strength, bioactivity, antibacterial activity, and controlled drug release are just a few of the many benefits that nanoparticles present because of their distinctive physical, chemical, and biological characteristics. In orthopedic and dental applications especially, bioactive nanoparticles such as hydroxyapatite and bioactive glass have been promising in enhancing tissue regeneration and osseointegration. Also, antimicrobial nanoparticles such as zinc and silver provide easy ways to hinder infections, a general problem with conventional implants. Also addressed in this paper is how nanoparticles can enable patient-specific implants to react dynamically to the body's needs, such as delivering drug therapy or responding to environmental stimuli. Challenges are there that need to be met, i.e., achieving scalable manufacturing procedures, being sure of biocompatibility, and maintaining long-term implant durability implants with nanoparticles inserted into them despite having many such developments already. Lately, emphasis has been placed on further development, e.g., combining nanoparticles with implant systems via 3D printing processes like FDM, SLA, and SLS. The study also discusses the regulatory environment and safety issues related to such new technology. Integrating functional nanoparticles into the 3D-printed biodegradable implants is a promising path towards developing tissue engineering, regenerative therapy, and personalized medicine. Still, more studies are required to overcome current challenges and make them clinically applicable.